Solvent screening, optimization and kinetic parameters of the biocatalytic epoxidation reaction of β-pinene mediated by Novozym®435 - Martins, Gustavo dos Santos; Staudt, Amanda; Sutili, Felipe Korbus; Malafaia, Camila Rodrigues Adão; Leal, Ivana Correa Ramos (Springer Nature, 2022)
Monoterpenes, such as beta-pinene, are secondary metabolites widely used in the flavors and fragrance industries and can have their structure altered to enhance their applicability, such as producing epoxides, which are used as intermediaries for pharmaceuticals. Epoxides are commonly synthesized by the use of inorganic acids as catalysts, although the acid medium induces epoxide degradation. To overcome these limitations biocatalysis is shown as an alternative. Related to, this work aimed to perform the synthesis of β-Pinene epoxide using Pseudozyma antarctica lipase B (Novozym®435) as a biocatalyst, while determining the independent variables that influence the reaction using experimental design tools. Different solvent systems were evaluated (cyclohexane, acetonitrile, ethyl acetate, and dichloromethane) until 72 h reaction time, from which ethyl acetate showed higher conversion into the epoxidized product (40% in 24 h). Under the other solvents systems, several oxidized by-products were obtained, such as ketones and aldehydes. Moreover, applying metrics of green chemistry, ethyl acetate was also corroborated as the most promising solvent, with a higher atom economy (66.8%) in comparison to the others (41.3%), and a smaller E-value (1.19). Ethyl acetate was the solvent/acyl donor of choice and had the molar ratio and percentage of biocatalyst increased, which resulted in 80% of the product after 3 h of reaction. To obtain an optimized model, four independent variables (temperature, stirring, molar ratio, percentage of biocatalyst) were evaluated using experimental design tools, Fractional Factorial Design and Central Composite Rotatable Design, with conversions ranging from 23 to 95% after 3 h. All the independent variables were statistically significant (p < 0.05) and had different degrees of impact on the conversion. Kinetic parameters of the reaction were determined using the Lineweaver–Burk model (results under 30.1 mmol for Km and 10.7 mmol.min−1 for Vmax). In conclusion, the combination of two different tools of experimental design provided the development of an optimized model for beta-Pinene epoxidation, achieving high conversion to the epoxidized product after 3 h.
Keywords: Beta-pinene; Biocatalysis; Epoxidation; Experimental design; Lipase; Novozym 435